Four versus 3 Cycles of Neoadjuvant Chemotherapy for Muscle-Invasive Bladder Cancer: Implications for Pathological Response and Survival. Issue 1 (27th January 2022) - Patel, Hiten D.; Patel, Sunil H.; Blanco-Martinez, Enrique; Kuzbel, Jake; Chen, Victor S.; Druck, Aleksander; Koehne, Elizabeth L.; Patel, Parth M.; Doshi, Chirag P.; Hahn, Noah M.; Hoffman-Censits, Jean H.; Berg, Stephanie; et al.
Abstract : Purpose: The ideal number of neoadjuvant chemotherapy (NAC) cycles for muscle-invasive bladder cancer is uncertain with 3 to 4 representing the standard of care (SOC). We compared ypT0 rates and survival between patients receiving 4 versus 3 cycles of NAC with evaluation of chemotherapy-related toxicity for correlation with tumor chemosensitivity and pathological response. Materials and Methods: Patients receiving NAC followed by radical cystectomy for cT2-4N0M0 urothelial carcinoma from 2 institutions were included. Primary study groups included 4 cisplatin-based NAC cycles, 3 cisplatin-based NAC cycles, and nonSOC NAC (1–2 cycles or noncisplatin-based) to compare ypT0/≤ypT1 rates and survival. A cohort of patients not receiving NAC was included for pathological reference. Results: Of 693 total patients, 318 (45.9%) received NAC. ypT0 and ≤ypT1 rates were 42/157 (26.8%) and 86/157 (54.8%) for 4 cycles, 38/114 (33.3%) and 71/114 (62.3%) for 3 cycles, and 6/47 (12.8%) and 13/47 (27.7%) for nonSOC (p=0.03 and p <0.01, respectively). Pathological response appeared higher among patients receiving 3 cycles due to toxicity (ypT0: 29/77 [37.7%]; ≤ypT1: 51/77 [66.2%]) but did not reach statistical significance. Toxicities leading to treatment modifications were thrombocytopenia (32.1%), neutropenia (27.2%), renal insufficiency (22.2%), and constitutional symptoms (18.5%). NonSOC patients had lower Kaplan-Meier survival (cT2-cT4N0M0: log-rank p=0.07; cT2N0M0: log-rank p=0.02). There were no statistically significant differences in survival between 4 and 3 cycles (HR 1.00 [95% CI 0.57–1.74], p=0.99). Conclusions: Patients completing 3 cycles of cisplatin-based NAC have similar pathologic response and short-term survival compared to 4 cycles. Further evaluation of patients experiencing toxicity as a potential marker of tumor chemosensitivity is needed.